A blinded, randomized, placebo‐controlled, dose determination trial of lokivetmab (ZTS‐00103289), a caninized, anti‐canine IL‐31 monoclonal antibody in client owned dogs with atopic dermatitis. Issue 6 (19th September 2016) - Michels, Gina M.; Ramsey, Deborah S.; Walsh, Kelly F.; Martinon, Olivier M.; Mahabir, Sean P.; Hoevers, Jacquelien D.; Walters, Rodney R.; Dunham, Steven A.
Abstract : Background: Pruritus is the hallmark clinical sign of atopic dermatitis (AD) in dogs. Lokivetmab, a caninized anti‐canine IL‐31 monoclonal antibody, reduced pruritus and associated inflammatory skin lesions in a proof‐of‐concept study in dogs with AD. Hypothesis/Objectives: The objective was to describe lokivetmab dose response in a randomized, double blind, placebo‐controlled trial. Animals: Clinicians at 15 referral clinics enrolled 211 client owned dogs with a history of chronic AD. Methods: Dogs were randomized to treatment with lokivetmab (0.125, 0.5 or 2.0 mg/kg) or placebo administered subcutaneously once on Day 0. Dog owners assessed visual analog scale (VAS) scores of pruritus on days 0, 1, 2, 3, 7, 14, 21, 28, 35, 42, 49 and 56. Clinicians assessed Canine AD Extent and Severity Index (CADESI‐03) scores on days 0, 7, 14, 28, 42 and 56. Results: Treatment with lokivetmab (2 mg/kg) resulted in a greater percentage reduction from baseline in owner assessed pruritus (days 1–49) and clinician assessed CADESI‐03 scores (days 7–56) compared to placebo ( P < 0.05 ); differences were achieved in lower dose groups but at later time points and for shorter duration for both owner assessed pruritus (0.5 mg/kg, days 2–35; 0.125 mg/kg, days 7–21) and clinician assessed CADESI‐03 scores (0.5 mg/kg and 0.125 mg/kg, Day 14). Conclusions and clinical importance: Lokivetmab (0.5, 2.0 mg/kg) reduced pruritus compared to placebo for at least 1 month. Level and duration of response increased with increasing dose. Further studies are needed to better understand variability in individual responses across a broader population of dogs with AD. Abstract : Background – Pruritus is the hallmark clinical sign of atopic dermatitis (AD) in dogs. Lokivetmab, a caninized anti‐canine IL‐31 monoclonal antibody, reduced pruritus and associated inflammatory skin lesions in a proof of concept study in dogs with AD.Hypothesis/Objectives – The objective was to describe lokivetmab dose response in a randomized, double blind, placebo‐controlled trial.Conclusions and clinical importance – Lokivetmab (0.5, 2.0 mg/kg) reduced pruritus compared to placebo for at least 1 month. Level and duration of response increased with increasing dose. Further studies are needed to better understand variability in individual responses across a broader population of dogs with AD.